Solriamfetol treatment of excessive daytime sleepiness in participants with narcolepsy or obstructive sleep apnea with a history of depression. (November 2022) - Krystal, Andrew D.; Benca, Ruth M.; Rosenberg, Russell; Schweitzer, Paula K.; Malhotra, Atul; Babson, Kimberly; Lee, Lawrence; Bujanover, Shay; Strohl, Kingman P.
Abstract: Given the high rate of depression associated with narcolepsy or obstructive sleep apnea (OSA), this analysis compared effects of solriamfetol treatment of excessive daytime sleepiness (EDS) in participants with/without a history of depression (DHx+/DHx-). This secondary analysis included data from two randomized, controlled trials in which participants were randomized to 12 weeks placebo or solriamfetol 37.5 (OSA only), 75, 150, or 300 mg/day. Efficacy/safety (combined solriamfetol doses) was summarized for DHx+/DHx-subgroups. 27.5% (65/236) with narcolepsy and 23.4% (111/474) with OSA were DHx+. In narcolepsy (DHx+ and DHx-), 40-min Maintenance of Wakefulness Test (MWT40) mean sleep latency increased (5.4 and 7.0 min), Epworth Sleepiness Scale (ESS) score decreased (3.8 and 3.5 points), and percentage of participants improved on Patient Global Impression of Change (PGI-C) was higher (31.7% and 39.4%) relative to placebo. In OSA (DHx+ and DHx-), MWT40 mean sleep latency increased (7.7 and 10.7 min), ESS decreased (3.5 and 3.7 points), and percentage of participants improved on PGI-C was higher (41.1% and 29.4%) relative to placebo. Common treatment-emergent adverse events (headache, decreased appetite, nausea, anxiety) were similar in DHx+/DHx-. This study suggests that safety and efficacy of solriamfetol for treating EDS in narcolepsy and OSA are not affected by depression history. Moreover, the findings emphasize the high prevalence of depression in people with sleep disorders and suggest that increased awareness of this association may have clinical significance. Graphical abstract: Image 1 Highlights: Solriamfetol treatment outcomes were analyzed according to depression history. Depression history was prevalent in people with narcolepsy/obstructive sleep apnea. Solriamfetol improved excessive daytime sleepiness regardless of depression history. Concomitant antidepressant use did not affect response to solriamfetol. Safety/tolerability was similar regardless of depression history/antidepressant use.